(3GdehGbas - (3YHO GdbGOQ Hf eMjj GdOjf Hf eUWaj GdMSfj GdLRGFQj,J (B1300 (3g` s
(3ChdgG (B:s
(3bGd JYGdi (B: ( (3hjVQH Gddg GdCeKGd ddfGS (B) (3hbGd JYGdi (B: ( (3Cf Gddg dG jSJMi Cf jVQH eKdkG eG HYhVI aeG ahbgG (B) (3hbGd (B: ( (3Jdc GdGeKGd fVQHgG ddfGS heG jYbdgG EdG GdYGdehf (B) s
(3BNQgG (B:s
(3bGd HYV GdGcGHQ jNGWH cHjQkG eKdg(B: (3aefge HgQL dGNjQ ajg hefge ef CQLhRI HHci hCfJ GdNGdU GdPgH GdeUai HbahcjJi heKdi ef jRci Je GdLRA GdKGfi ef GdehGba HYhf Gddg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B45s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG s
Keywords: (3GdbQGAGJ hGdJLhjOs